Keunikan Struktur Anatomi dan Morfologi Burung Maleo (Macrochepalon maleo) sebagai Fauna Endemik Indonesia dan Upaya Konservasinya - Manalu, Damai Y.; Rido, Elisabeth M.T.; Irawati, Wahyu (Jurnal Biologi Papua, 2023)
Maleo bird is one of the unique animals of the aves class which is included in endemic animals in Indonesia. The Maleo bird is almost endangered due to predators and irresponsible behavior of local people. One of the conservation efforts carried out by the government is contained in Law No. 5 of 1990 and Government Regulation No. 7 of 1999 concerning the protection or conservation of Maleo birds. The purpose of this paper is to analyze the morphological and physiological characteristics of the Maleo bird (Macrochepalon maleo), the anatomy of the Maleo bird (Macrochepalon maleo), the relationship of the uniqueness of the behavior of the Maleo bird (Macrochepalon maleo)  with the morphology, anatomy, and physiology of the Maleo bird, as well as conservation efforts of the Maleo bird (Macrochepalon  maleo). The method used is a literature review by reading various books, journals and papers and other publications in accordance with the research topic. The results of research that have been conducted show that the morphology, anatomy, and physiology of the Maleo bird are closely related to the behavior of the Maleo bird. The Maleo bird uses a crest located on its head to detect heat when digging an egg nest. Maleo bird legs equipped with sharp hooves can make Maleo birds able to survive in coastal forests. Maleo birds are monogamous animals, namely animals that are loyal to their partners. The advice that can be given through this literature review is that the community must have awareness to take care of the Maleo bird as a form of accountability for the mandate given by God to humans. Key words: Aves; endemic; conservation; maleo; morphology